Let quenching correction in solid state dosimeters. (September 2016) - Gambarini, G.; Artuso, E.; Camoni, G.; Colombo, G.; Felisi, M.; Gebbia, A.; Massari, E.; Veronese, I.; Giove, D.; Carrara, M.; d'Errico, F.
Abstract : Introduction: The increasing improvement and application of hadrontherapy calls for appropriate dosimetric methods. A general limit of solid state dosimeters is the quenching of the sensitivity with increasing radiation LET. Purpose: Aims of this work are the study of the quenching phenomena observed in various dosimeters exposed to charged particles, and the development of a reliable, general method to amend the measured values in order to achieve correct dose values. Materials and methods: The investigated dosimeters were laboratory-made Fricke-gel dosimeters, gafchromic EBT3 films and thermoluminescence detectors (TLDs). Fricke-gel dosimeters and EBT3 films were analyzed by detecting variations in optical density (ΔOD). In photon fields, ΔOD is proportional to the absorbed dose, but in charged particles fields it is affected by the quenching effect. TLDs were read out with a Harshaw/Bicron TLD unit. Irradiations were performed with photons, protons of various energies and charged particles generated by thermal neutrons. Results: A method for correcting the 2D dose maps acquired with gel dosimeters and EBT3 films exposed to hundreds of pencil beams of protons (as is done in radiotherapy) is proposed. The response correction is done with our original code that utilizes the treatment plan file as input data. Our algorithms are based on quenching correction maps obtained by comparing measured and calculated Bragg peaks images. Analogous methods for TLDs are in development. Conclusion: The proposed methods for amending the dosimeter responses have proved to be very promising. Disclosure: Authors declare no relationship that may bias the presentation.